Health-related quality of life after esophagectomy in patients with esophageal cancer - Toh, Yasushi; Morita, Masaru; Yamamoto, Manabu; Nakashima, Yuichiro; Sugiyama, Masahiko; Uehara, Hideo; Fujimoto, Yoshiaki; Shin, Yuki; Shiokawa, Keiichi; Ohnishi, Emi; Shimagaki, Tomonari; Mano, Yohei; et al. (Esophagus : official journal of the Japan Esophageal Society, 2022)
Esophageal cancer is one of the malignant tumors with the poorest prognosis. Esophagectomy, which is the mainstay of curative-intent treatments, imposes excessive surgical stress on the patients, and postoperative morbidity and mortality rates after esophagectomy remain high. On the other hand, the number of survivors after esophagectomy for esophageal cancer is increasing due to recent improvements in surgical techniques and multidisciplinary treatments for this cancer. However, esophagectomy still has a great influence on the fundamental aspect of patients’ lives, that is, the health-related quality of life (HR-QOL), including their physical, emotional, and social functions in the short- and long-term postoperatively. HR-QOL is a multifactorial concept used to assess the symptoms and functional changes caused by the disease itself and treatments from the patients’ perspectives. Therefore, assessing the HR-QOL of patients with esophageal cancer after esophagectomy is becoming increasingly important. However, the status of HR-QOL changes after esophagectomy has not been satisfactorily evaluated, and there is no worldwide consensus as to how the postoperative HR-QOL can be improved. This review aimed to raise awareness of healthcare providers, such as surgeons and nurses, on the importance of HR-QOL in patients with esophageal cancer after curative-intent esophagectomy by providing multifaceted information concerning the short- and long-term HR-QOLs, including the status of changes and the determinants of HR-QOL after esophagectomy, and furthermore, essential points for improvement of HR-QOL after esophagectomy.